Nilai-Nilai Pendidikan Karakter Pada Ajaran Mahabah Perspektif Robi’ah Al- Adawiyah - Mihmidaty Ya'cub; Windi Aprilia Robiati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Character education has become a major concern in the world of contemporary education. This article proposes a new approach to integrating the values of character education in the Islamic context through the Mahabah teachings, which are based on the concepts of love, compassion, and love. The perspective of Robi’ah al-Adawiyah, a prominent Sufi figure, was used as a basis for explaining this concept. This article carries out research methods using a library research approach, collecting and analysing data from relevant literary sources. The results of the analysis identify key concepts in Mahabah teachings, such as love, compassion, respect, honesty, and humility, which can be applied in the context of contemporary character education. In the context of character education, these values form the basis for forming individuals with strong morality, integrity, and the ability to contribute positively in an increasingly complex society. This article also highlights the relevance of Mahabah values in an increasingly multicultural society and offers insights into how character education can be more holistic by integrating spiritual and moral values as taught by Robi’ah al-Adawiyah. By combining the teachings of Mahabah and Robi’ah al-Adawiyah’s thinking, this article seeks to provide a richer and deeper insight into the values of character education in the Islamic context. Through this deeper understanding, the article contributes to the development of a more holistic and sustainable education that not only produces individuals who are academically intelligent but also have high moral integrity